An evaluation of clinical facilitation in the Nursing College of the Eastern Cape province - Peter, Zingiwe Patricia (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MCur (Nursing Science))--University of Stellenbosch, 2008.